(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disorder characterized by persistent synovial inflammation, progressive joint destruction, and significant functional disability. Although conventional anti-arthritic therapies are effective, their long-term use is often associated with adverse effects, necessitating the search for safer and more effective therapeutic alternatives from medicinal plants. Sida acuta, a well-known medicinal plant in traditional medicine, possesses diverse pharmacological properties, including anti-inflammatory activity. Objective: The present study aimed to investigate the in vitro anti-arthritic activity of the ethyl acetate and chloroform extract of Sida acuta using the bovine serum albumin (BSA) protein denaturation assay. Methods: The anti-arthritic activity of the ethyl acetate and chloroform extracts were evaluated by assessing its ability to inhibit heat-induced protein denaturation. The extracts were tested at different concentrations, and diclofenac sodium was used as the standard reference drug. The percentage inhibition of protein denaturation was calculated and compared with that of the standard. Results: The ethyl acetate and chloroform extracts of Sida acuta exhibited significant, concentration-dependent inhibition of protein denaturation, indicating promising anti-arthritic activity. The observed pharmacological effect may be attributed to the presence of bioactive phytoconstituents, particularly flavonoidal glycosides and other secondary metabolites, which are known to possess anti-inflammatory properties. Conclusion: The findings of the present study demonstrate that the ethyl acetate and chloroform extracts of Sida acuta possesses considerable in vitro anti-arthritic activity and supports its traditional use in the management of inflammatory disorders. These results suggest that Sida acuta may serve as a potential natural source for the development of novel anti-arthritic agents. Further phytochemical characterization, in vivo pharmacological studies, and mechanistic investigations are warranted to validate its therapeutic potential.